An illustrated atlas for male genitalia of the New World Polistes Latreille, 1802 (Vespidae: Polistinae) - Somavilla, Alexandre; Oliveira, Marcio Luiz; Andena, Sergio Ricardo; Carpenter, James Michael (Zootaxa, 2018)
The male genitalia of 58 species of the New World Polistes are described: 29 of Polistes (Aphanilopterus), 12 of Polistes (Epicnemius), 13 of Polistes (Fuscopolistes), one of Polistes (Onerarius) and three of Polistes (Palisotius). Comments and remarks are also provided.